Report of chronic myeloid leukemia in chronic phase from Ashirwad Hematology Centre, Mumbai, 2002-2009 - Agarwal, M G; Agarwal, Usha M; Rathi, Shonali S; Masurkar, Sangeeta; Zaveri, Bindi (Indian Journal of Medical and Paediatric Oncology, 2013)
We have analyzed our experience regarding use of tyrosine kinase inhibitors especially imatinib mesylate in patients of chronic myeloid leukemia-chronic phase over last 7 years at our center (2002-2009). The object was to report long-term efficacy (hematological, cytogenetic and molecular) and toxicity. Overall, 775 patients were treated. Out of these, 576 were analyzable with a median follow-up of 3.6 years. The median age was 42 years. Complete cytogenetic response (CCyR) was achieved in 351/576 patients, i.e., 62.1%. Grade 3/4 adverse effects were observed in 36 patients, i.e., 6.25%. Age under 40 years, low Sokal score, complete hematological response and CCyR were significant predictive factors for event free survival (EFS) on univariate analysis while low Sokal score and early chronic phase were significant predictive factors for EFS on multivariate analysis. Our results are almost similar to those reported from various studies from western population.
Keywords: Chronic myeloid leukemia; cytogenetic response; imatinib mesylate; India; molecular response; toxicity